(3QSGdI aj GdCSYGQs - (3CMeO Hf eMeO Hf YHO GdLdjd GdSLRj, CHh SYjO,J (B477 (3g` s
(3ChdgG (B:s
(3cJGH GdGSYGQ JCdja CMeO Hf eMeO Hf YHO GdLdjd bO jQO Gf jSJCfa QSGdI ai GdeYfi GdPi jTJed Ydjg MGd GdGSYGQ s
(3BNQgG (B:s
(3HBNQg hbaI cGJH BNQgG GdLedI GdYGTb ai GdGYJHGQGJ BNQ bhd GdbOeGA hGdeMOKjf heG bO LQHfG ai ReGffG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B213 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B271 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B80s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi s
Keywords: (3GdQjGVjGJs